Armed robbers : identity and cultural mythscapes in the lucky country - Taylor, Emmeline (Convenor of criminology) (Oxford : Oxford University Press, 2022)
This title offers a frank account of the experiences of convicted armed robbers suffused with moral ambiguities. Notoriously difficult to access, armed robbers have mostly eluded the attempts of authors to access their lives. Aside from biographies of the most infamous, the stories of armed robbers, as varied, bizarre, and captivating as they are, have rarely been told. This has resulted in robbers being considered as largely homogenous; their unique pathways to crime ignored or lumped into ill-defined stereotypes. Yet their routes into one of the most serious violent crimes could not be more varied. Written by a leading female criminologist, 'Armed Robbers' relays the powerful, sometimes amusing, often harrowing stories of 42 convicted criminals in Australia.
This edition also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on April 8, 2022).
Keywords: Robbery -- Australia -- History